Constructing the understanding of teenagers deviant use of cyberspace. (December 2021) - Sharma, Manoj Kumar; Anand, Nitin; Kumar, Keshav; Lenin Singh, Rajkumar; Thakur, Pranjali Chakraborty; Mondal, Ishita; Kohli, Tavleen
Cyberspace provides a completely different platform for the expression of one's needs in comparison to the face-to-face world. The use of cyberspace by teenagers is becoming a major concern due to the emergence of engagement in deviant use of internet applications inclusive of engagement in sexting; excessive and addictive use of the internet, consumption of pornography, and as well as phenomena of internet chat rooms. The online disinhibition, anonymity, personality factors, sensation-seeking behavior, impulsivity, deviant socialization processes, and absence of social systems to educate adolescents about gender sensitivity and sex appear to predispose teenagers for indulgence in deviant usage of cyberspace. There is an urgent need to understand the factors related to deviant use of cyberspace and for offering programs for parents and adolescents on gender sensitivity, sexuality, sex, consent in relationships, and deviant use of internet applications. Such initiatives will help to offer opportunities for a corrective experience through appropriate socialization experiences and enhance cyberliteracy among children and adolescents.